A low-cost photoelectrochemical tandem cell for highly-stable and efficient solar water splitting. (November 2017) - Zeng, Qingyi; Bai, Jing; Li, Jinhua; Zhou, Baoxue; Sun, Yugang
Abstract: The stability and cost of solar-driven water splitting system are still the main bottlenecks for its large-scale implementation. Here, an ingeniously designed low-cost photoelectrochemical tandem cell possessing three performance-superior components, i.e., a front novel photoanode of WO3 nanoplates epitaxially coated with [001]-oriented TiO2 nanoprickles, and a rear Si photovoltaic cell, and a counter-cathode of interlayer-expanded MoS2 nanostructures, is reported for highly-stable and efficient solar water splitting. The tandem cell shows a close-to-unity Coulomb efficiency for water splitting, and a high and sustained-stable solar-to-hydrogen efficiency in a 35 days' test. The result also reveals that it is versatile in solar-driven wastewater treatment. Most importantly, the composite photoanode that, for the first time, is proposed using epitaxial-growth based on double-match, i.e. lattice match and band match, shows dramatical improvement in stability and photoelectrochemical performance, in which the photocurrent of the WO3 / TiO2 photoanode is improved by 80% without any obvious decay after 100 h of continuous testing compared with a 92% decay in photocurrent for the WO3 photoanode. The epitaxial TiO2 layer facilitates interfacial charge transportations and provides a complete sealing of WO3 surfaces at an atomic level. Such efficient interfacial design and system-level integration of high-performance nanomaterials shed a unique light on the potential large-scale implementation of solar water splitting for renewable hydrogen fuel production. Graphical abstract: An ingeniously designed low-cost photoelectrochemical tandem cell possessing three performance-superior components, i.e., a front novel photoanode of WO3 nanoplates epitaxially coated with [001]-oriented TiO2 nanoprickles, and a rear Si photovoltaic cell, and a counter-cathode of interlayer-expanded MoS2 nanostructures, is reported for highly-stable and efficient solar water splitting. Highlights: Low-cost PEC tandem cell is designed for high stability and efficient water splitting. [001]-oriented anatase TiO2 nanoprickles can epitaxially grow on WO3 nanoplates. WO3 /TiO2 NP photoanode overcomes the shortages of both WO3 and TiO2 photoanodes. PEC tandem cell shows a high and sustained-stable STH efficiency over 35 days of testing.